Mental health professionals’ experiences of working with parents with psychosis and their families: a qualitative study - Radley, J; Barlow, J; Johns, L (BioMed Central, 2021)
Background Healthcare service users who are parents with psychosis form part of the caseload of most community mental health teams. Mental health professionals can experience uncertainty about how to work with and ask about the children of these parents, and often report difficulties when collaborating with other agencies. This study focused on professionals’ experiences of working with parents with psychosis and their families to gain an understanding of these parents’ needs from a service-level perspective, and to identify barriers that professionals may experience in meeting those needs. Methods Qualitative focus groups were conducted with four to eight mental health professionals per group. Data were analysed using reflexive thematic analysis. JR familiarised herself with the transcripts and then coded each salient unit within the text. Themes were then identified and discussed amongst all authors until there was agreement. Results We developed two overarching themes: 1) Diversity of need in parents with psychosis and 2) Role boundaries. The first explored mental health professionals’ perceived range of experiences that parents with psychosis and their families have, and the range of potential effects of parental psychosis on a child. The second theme described how some mental health professionals emphasised the importance of supporting service users in terms of their parenting status and others felt it was more critical to treat the person’s symptomatic expression. This theme also included issues with communication both with their service users and with other agencies. Conclusions Mental health professionals identified that the needs of parents with psychosis were diverse and reflected significant variation in the experiences of service users. Mental health professionals across different types of team (early intervention and community mental health) expressed contrasting viewpoints about how achievable it was to respond to a service user’s parenting status in an adult mental health setting. Future research should aim to determine where training is needed to enhance mental health professionals’ ability to work holistically with families in an adult mental health setting, and how to enhance collaboration with other agencies.